2019
DOI: 10.1002/jclp.22903
|View full text |Cite
|
Sign up to set email alerts
|

Rural mental health service utilization in a Texas telepsychology clinic

Abstract: Objective: To determine if service utilization behaviors varied with the remoteness of clients served by a telepsychology clinic in a predominantly rural health professional shortage area (HPSA) in Texas. Methods: Archival data from 290 low-income clients wereanalyzed to test associations between service utilization behaviors and clients' distance from the nearby access points where they traveled to receive counseling services from remotely located counselors.Results: Distance to access points did not predict … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…At a systemic level, the role of telemedicine in behavioral health is particularly salient in Texas, with its status of having the most rural-residing residents of all states, and the fact that the vast majority of MHPs in Texas work in just 5 out of the state’s 254 counties ( Tarlow et al, 2020 ). In a longitudinal study on Texas individuals with depression, self-reported severe disruptions to daily routines and disruptions in access to mental health treatment in having appointments canceled or postponed led to greater depressive and anxiety symptoms in the early pandemic period (May–August 2020) relative to pre-pandemic levels ( Czysz et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…At a systemic level, the role of telemedicine in behavioral health is particularly salient in Texas, with its status of having the most rural-residing residents of all states, and the fact that the vast majority of MHPs in Texas work in just 5 out of the state’s 254 counties ( Tarlow et al, 2020 ). In a longitudinal study on Texas individuals with depression, self-reported severe disruptions to daily routines and disruptions in access to mental health treatment in having appointments canceled or postponed led to greater depressive and anxiety symptoms in the early pandemic period (May–August 2020) relative to pre-pandemic levels ( Czysz et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this model, treatment is provided in-person either one-to-one or in a group by a highly trained mental health professional within a clinical setting. The reliance of this model on trained professionals has become a problem due to the lack of mental health service providers, especially in remote and rural areas [87][88][89][90][91][92][93]. However, in the recent times, telepsychology, which entails the provision of conventional mental health services using telecommunications technology, such as telephones, smartphones, and virtual conferences, has significantly increased and improved access to treatment services [88,[93][94][95][96][97].…”
Section: Current Assistive Technologies For Mental Healthmentioning
confidence: 99%
“…The reliance of this model on trained professionals has become a problem due to the lack of mental health service providers, especially in remote and rural areas [87][88][89][90][91][92][93]. However, in the recent times, telepsychology, which entails the provision of conventional mental health services using telecommunications technology, such as telephones, smartphones, and virtual conferences, has significantly increased and improved access to treatment services [88,[93][94][95][96][97]. Studies have shown that telepsychology is a reliable method of treatment and people both in rural and urban areas are receptive to it [94][95][96].…”
Section: Current Assistive Technologies For Mental Healthmentioning
confidence: 99%
“…Lack of quality broadband access is a well-documented concern regarding the delivery of high-quality telehealth services (Benda et al, 2020). Other barriers include overcoming stigma, lower technology literacy, lower rates of insurance, and geographic and transportation barriers in the hub and spoke models (Crosby et al, 2012; Syed et al, 2013; Tarlow et al, 2020). Given the already small population sizes inherent in rural areas, compounded with the barriers to accessing care even when made available through telehealth, studying the effectiveness of teletherapy in rural areas can be challenging.…”
Section: Research Questionsmentioning
confidence: 99%